Forming of practical experience in the execution of programme tasks of discipline "Principles of external advertisement" - V.V. Tomashevsky (Academy of Cognitive and Natural Sciences, 2006)
In article is considered the questions of forming of practical experience in the execution of programme tasks of discipline "Principles of external advertisement" in preparing of teacher Fine Art.